2019
DOI: 10.1093/nar/gkz444
|View full text |Cite
|
Sign up to set email alerts
|

A long noncoding RNA cluster-based genomic locus maintains proper development and visual function

Abstract: Long noncoding RNAs (lncRNAs) represent a group of regulatory RNAs that play critical roles in numerous cellular events, but their functional importance in development remains largely unexplored. Here, we discovered a series of previously unidentified gene clusters harboring conserved lncRNAs at the nonimprinting regions in brain (CNIBs). Among the seven identified CNIBs, human CNIB1 locus is located at Chr 9q33.3 and conserved from Danio rerio to Homo sapiens. Chr 9q33.3-9q34.11 microdeletion has previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…In functional assays, knockdown of 7SK in cell and xenograft experiments showed a tumor suppressor role of 7SK in TSCC. Numerous reports have linked non-coding RNAs with cancer ( Wapinski and Chang, 2011 ; Wang et al, 2019 ; Huang et al, 2020 ). For example, HOTAIR is found to be associated with tumor metastasis in breast cancer through binding with polycomb repressive complex 2 (PRC2) and the lysine-specific demethylase1 (LSD1) to regulate gene expression ( Burd et al, 2010 ; Tsai et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In functional assays, knockdown of 7SK in cell and xenograft experiments showed a tumor suppressor role of 7SK in TSCC. Numerous reports have linked non-coding RNAs with cancer ( Wapinski and Chang, 2011 ; Wang et al, 2019 ; Huang et al, 2020 ). For example, HOTAIR is found to be associated with tumor metastasis in breast cancer through binding with polycomb repressive complex 2 (PRC2) and the lysine-specific demethylase1 (LSD1) to regulate gene expression ( Burd et al, 2010 ; Tsai et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous RNA-Seq data showed that GAS5 had differential expression patterns in young and old mice brains, which suggested that it may participate in brain aging ( Wang et al, 2019 ). Further examination using RT-qPCR on four different brain tissues confirmed that GAS5 is expressed significantly higher in the old mouse brain hippocampus region comparing with that of a young mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous RNA-Seq data showed that GAS5 exhibits differential expression patterns in young and old mice brain tissues, which suggested that it may play a role in brain aging ( Wang et al, 2019 ). Thus, we conducted various experiments on mice brain tissues and brain-derived cell lines to explore the role and underlying mechanism of GAS5 in senescence and brain aging.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA Pnky is a trans-acting regulator of cortical development in vivo [26]. Wang et al demonstrate that conserved lncRNAs at the nonimprinting regions in brain are essential for zebra sh development [27].…”
Section: Introductionmentioning
confidence: 99%